2022
DOI: 10.1158/0008-5472.can-22-0325
|View full text |Cite
|
Sign up to set email alerts
|

An Immunogenic Model of KRAS-Mutant Lung Cancer Enables Evaluation of Targeted Therapy and Immunotherapy Combinations

Abstract: Mutations in oncogenes such as KRAS and EGFR cause a high proportion of lung cancers. Drugs targeting these proteins cause tumor regression but ultimately fail to elicit cures. As a result, there is an intense interest in how to best combine targeted therapies with other treatments, such as immunotherapies. However, preclinical systems for studying the interaction of lung tumors with the host immune system are inadequate, in part due to the low tumor mutational burden in genetically engineered mouse models. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(92 citation statements)
references
References 46 publications
3
71
1
Order By: Relevance
“…We did not find any macroscopic evidence of reproducible changes in any organs that would be consistent with ADAR1 overexpression, or its individual isoforms p110 or p150, leading to formation of tumors in vivo. It has been demonstrated using analogous models that the C-to-U base editor APOBEC3 will induce tumors in mice following overexpression in vivo, demonstrating that such systems will yield in vivo cancer if the overexpressed protein can function as an oncogene (94)(95)(96). Based on the two models we proposed, we did not find evidence to support the conclusion that ADAR1 was functioning as an oncogene.…”
Section: Discussioncontrasting
confidence: 56%
“…We did not find any macroscopic evidence of reproducible changes in any organs that would be consistent with ADAR1 overexpression, or its individual isoforms p110 or p150, leading to formation of tumors in vivo. It has been demonstrated using analogous models that the C-to-U base editor APOBEC3 will induce tumors in mice following overexpression in vivo, demonstrating that such systems will yield in vivo cancer if the overexpressed protein can function as an oncogene (94)(95)(96). Based on the two models we proposed, we did not find evidence to support the conclusion that ADAR1 was functioning as an oncogene.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, in lung cancer, SHP2 inhibitors induce CXCR2 ligands that recruit myeloid derived suppressor cells and limit the response to this therapy 18 . Multiple groups including ours have recently demonstrated the involvement of anti-tumor immunity in the therapeutic response to KRAS G12C inhibitors 10,12,13,15 . We recently reported the involvement of adaptive immunity in the therapeutic response of murine lung cancer cells driven by oncogenic EGFR to the TKI, osimertinib 14 .…”
Section: Quantification Of Lymphocytes and Pmns In Alk+ Patient Biopsiesmentioning
confidence: 96%
“…Our recent published studies demonstrate that EGFR-targeted inhibitors induce an interferon (IFN) response program that varies markedly between distinct EGFR mutant lung cancer cell lines and positively associates with the duration of therapeutic response in EGFR-mutant lung cancer patients 7 . In fact, there is a growing literature supporting the role of host immune cells in overall therapeutic response to precision oncology agents and cytotoxic drugs [8][9][10][11][12][13][14][15][16][17][18][19] . However, the mechanisms whereby TKIs induce factors mediating paracrine signaling to the immune microenvironment, and the contribution to the overall therapeutic response are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that KRAS-SHP2-MAP kinase pathway-targeted agents induce expression of multiple chemokines in KRAS-mutant lung cancer cell lines ( 21 , 44 , 45 ) and may provide a mechanism by which oncogene-targeted drugs induce cross-talk between cancer cells and the tumor microenvironment. Interrogation of RNAseq data generated from LLC 46 NRAS KO, CMT-KRAS-G12C.54 and mKRC.1 cells treated in vitro for 6 hr to 3 days with 30 nM MRTX-1257 reveals distinct expression patterns of chemokines with defined anti- and pro-tumorigenic functions ( 46 ) ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…The murine KRAS G12C -driven lung cancer cell lines developed in this study provide novel models to investigate KRAS G12C inhibitor responsiveness in the immune competent setting. This is critical since oncogene-targeted agents including KRAS G12C inhibitors have been shown to initiate functional interactions with host immunity ( 27 , 28 , 34 , 44 , 45 ). The new lung cancer cell lines described herein uniformly exhibit high in vitro sensitivity to KRAS G12C inhibitors and altered growth signaling in CMT KRAS G12C clones compared to parental G12V cells.…”
Section: Discussionmentioning
confidence: 99%